The implication of tax rates on corporate capital investment / Nor Shaipah Abdul Wahab... [et al.] - Abdul Wahab, Nor Shaipah; Aripin, Norhani; Md Idris, Kamil (Accounting Research Institute (ARI) & Faculty of Accountancy, 2007)
The purpose of this study is to determine the relationship of tax rates and corporate capital investment behavior. In addition, this study seeks to investigate the influence of tax rates reductions on capital investment. A total of 120 companies were selected as the sample. The findings demonstrated that there are significant negative associations between corporate tax rate and non-resident individual tax rate reduction with corporate capital investment. In addition, the results revealed the significant influence of market-to-book equity ratio and lagged investment on capital investment. With respect to industry classification, property and plantation industries are found to be significant and negatively associated with capital investment. This research would be useful to the authorities in determining the implication of tax rate reduction on capital investment, which in turn will reflect the overall economy.